Advances in human factors in energy : oil, gas, nuclear and electric power industries : proceedings of the AHFE 2017 International Conference on Human Factors in Energy: Oil, Gas, Nuclear and Electric Power Industries, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: oil, gas, nuclear and electric power industries : proceedings of the AHFE 2017 International Conference on Human Factors in Energy: Oil, Gas, Nuclear and Electric Power Industries, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available